Networking among College Libraries in Nagaland (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The advent of computer networks ushers a new path to the traditional jobs of the library such as retrieval and dissemination of information. Modern library collaboration is a direct result of the proliferation of internet databases and resource sharing networks. Libraries have profited substantially from the expansion of their access to information resources made possible by the Internet and other networks. The value of resource sharing networks among Nagaland's university libraries is the central argument of this article. Colleges that are associated with Nagaland University are the ones that students choose to attend. Sharing resources is now a possibility because to advancements in information and communication technologies. Consequently, school libraries in Asian countries need a system for exchanging resources and networking. A resource sharing network may be easily constructed in any Asian nation. In addition to bringing people together as a global village, the internet now has the potential to unite all of the world's libraries into a single global library via the development of resource-sharing networks. Looking at the bigger picture, it seems that Resource Sharing might be a great benefit that has to be implemented more consistently and expertly in Asian countries university and faculty libraries. This programme has the potential to save significant amounts of government resources while simultaneously making people very happy.